An Assessment of the Rehabilitation of Convicts in Kazakhstan - Anuarbek, Yersin; Zharkenova, Tokzhan (Nazarbayev University Graduate School of Public Policy, 2020)
In the last five years, Kazakhstan faced a radical change in the penal system. One of the challenges was the introduction of the probation and rehabilitation program that helps to integrate convicts back into society. The research looked at the employment of ex-offenders because it helps to prevent issues with housing, health problems, and sustaining family. It reduces the major problem - recidivism. Employment is a vital need for every individual that helps to feel included in society, to earn money, and feel self-worth. This study showed that there are barriers for some groups of people to be employed. One of the crucial obstacles can be a criminal past, which makes it problematic for employers to hire ex-offenders. Many reasons can influence the probability and chance to be employed. Several research studies have shown that incarceration makes a set of obstacles: type of job available in the market, individual motivation, remuneration, skills, and knowledge. Paper discusses in detail the difficulties and barriers of ex-offenders in securing employment. Qualitative analysis of interviews and secondary data analysis were conducted for the research. The study focused on the correlation between employment and rehabilitation programs in Kazakhstan, with references to the practice of different countries. Then the recommendations were given as the measures to overcome the employment issues.